Madr-i-Millat Mohtarma Fatima Jinnah : A Chronology (1893-1967) - Compiled by Prof. Dr. Riaz Ahmad (Islamabad NIHCR, 2003)
Fatima Jinnah, 1894-1967, Pakistani politician and sister of Mohammed Ali Jinnah.
Include Color Illustration, Bibliography and Index
Keywords: Jinnah, Fatima, -- 1894-1967 -- Chronology